Use of the total physical response as a teaching strategy in improving the acquisition of new vocabulary in the english language. - Tacuri Moyano, Jonathan Ariel; Jarre Ibáñez, Doménica Paulette (Machala: Universidad Técnica de Machala, 2024)
The present research focuses on the implementation of Total Physical Response TPR as a teaching strategy to improve English vocabulary acquisition among elementary students at the N.A Basic Education School. The study employed theoretical and empirical methods to structure the research and collect data. A mixed-method approach was applied, with an experimental and explanatory design, allowing for validating the scientific hypothesis regarding the influence of TPR. Additionally, instruments such as pre-test, post-test, observation guides, and interviews were used to measure the initial and final performance of the 36 students, followed by the implementation of a class system based on the strategy mentioned above to address learning deficiencies
La presente investigación se enfoca en la implementación del Total Physical Response TPR como estrategia de enseñanza para mejorar la adquisición de vocabulario en inglés en los estudiantes de básica elemental de la Escuela de Educación Básica N.A. Se emplearon métodos teóricos y empíricos para estructurar el estudio y recolectar datos. La investigación se realizó bajo un enfoque metodológico mixto, con un diseño experimental y explicativo, permitiendo comprobar la hipótesis científica sobre la influencia del TPR. Adicionalmente, se utilizó instrumentos tales como pre-test, post-test, guía de observación y entrevistas para medir el desempeño inicial y final de los 36 estudiantes, seguido de la implementación de un sistema de clase basado en la estrategia ya mencionada para tratar las deficiencias en el aprendizaje.
Keywords: TOTAL PHYSICAL RESPONSE; ADQUISICIÓN DE VOCABULARIO; ENSEÑANZA DE INGLES; EDUCACIÓN BÁSICA